Pengukuran Penerimaan Pembelanja Daring terhadap E-Marketplace Menggunakan Modifikasi UTAUT - Asif Faroqi; Apol Subriadi P (INTEGER: Journal of Information Technology, 2017)
One of the fastest growing e-commerce business model is e-marketplace. Competition between e-marketplace also took place tight, thus causing an e-marketplace more successfull than other e-marketplace. An e-marketplace is said to be successful and can survive if accepted by users, both from buyers and sellers. Therefore understanding the motivation of people in using e-marketplace is necessary. Most of the existing research has analyzed this only from the external motivation of e-marketplace acceptance by users. This study discusses intrinsic and extrinsic motivation that impact on the acceptance of e-marketplace by internet users, espesially online shoppers in Indonesia. This study uses the expanded of Unified Theory of Acceptance and Use of Technology by adding a shopping enjoyment construct as part of the flow theory to represent the intrinsic motivation of e-marketplace users. The sample of this study takes the subject of students, workers and housewives. This is based on the result of a 2015 APJII survey which state that the largest internet users in Indonesia is a worker or a self-employed (62%), housewives (16,6%) and students (7,8%). The results of this study are expected to provide information about the motivation of acceptance of e-marketplace by internet users, espesially online shoppers. It is expected to be an input for e-marketplace service providers to make improvements to its service.Keywords: UTAUT, Technology Acceptance Theory, E-marketplace, Shopping enjoyment